(untitled) (Research, Society and Development, 2022)
Cocoa (Theobroma cacao), is an economically important crop in several tropical countries. In Brazil, the cocoa agroindustry occupies a place of expression in the north and northeast regions, which stands out among those used in seed production, as they are used as raw material for chocolate manufacturing, and the pulp of these fruits is little used in the food industry. The cajá (Spondias mombin), has wide tropical distribution, this fruit is, today, cultivated in the North and Northeast regions, and can also be known as taperebá, is of flavor, aroma and color suitable for the conquest of the most demanding palates. The study in question aimed to characterize the pulp of cocoa and cajá fruits, as well as color evaluation. The fruits were collected in the city of Conceição do Araguaia (PA), and then transported to a fruit processing plant based in the same municipality, where they went through technological processes to obtain fruit pulps. Where they were forwarded and stored at controlled temperature in the laboratory of fruit and vegetable technology of the Federal University of Tocantins of the Food Engineering Course. The analyses that were performed on the pulps are: pH, soluble solids, acidity, lipids, moisture, total solids, vitamin C, ash, total fiber, and instrumental color parameters (L, a*, b*, C and H), results obtained, demonstrated that the pulps are in accordance with normative instruction No. 37/2018 of MAPA, for analytical parameters and requirements complementary to the standards of identity and quality of fruit pulp.